Which Abortion Patients Have Had a Prior Abortion? Findings from the 2014 U.S. Abortion Patient Survey - Jones, Rachel (J Womens Health (Larchmt), 2018)
Background: Updated information about abortion patients who have had a prior abortion could inform patient-centered practices that help women avoid unintended pregnancies in the future. Materials and Methods: Data come from a national sample of 8,380 nonhospital U.S. abortion patients accessing services at 87 facilities. The dependent variable was a self-reported measure of prior abortion. Bivariate and multivariable analyses were used to assess associations between a range of demographic and circumstantial characteristics and reports of obtaining a prior abortion. Results: We found that 45% of patients reported having one or more prior abortions. Age was most strongly associated with this outcome, and patients aged 30 and older had more than two times the odds of having had a prior abortion compared with those aged 20–24. Other characteristics associated with an increased likelihood of prior abortion included having one or more children, being black, relying on insurance or financial assistance to pay for the procedure, and exposure to disruptive events in the last 12 months. Characteristics associated with a decreased likelihood of having a prior abortion included having a college degree and living 25 or more miles from the facility where the current abortion was obtained. Conclusions: Age is the biggest risk factor for having had a prior abortion; the longer a woman has been alive, the longer she is at risk of unintended pregnancy. Some characteristics associated with prior abortion were beyond the control of the individuals experiencing them.